Composición química y degradabilidad in situ de residuos agrícolas de maíz inoculados con dos cepas del género pleurotus. finca la María. 2012. - Peña Gáleas, Mayra Mercedes (2013)
This research was carried out in order to evaluate the chemical composition and in situ degradation of inoculated agricultural corn stover with two strains of fungus (genus Pleurotus). Three groups of corn stover (only stubble, only cobs, and a mixture of stubble and cobs) were inoculated with P. ostretus and P. sapidus for a period of 21 days of solid-state fermentation. The effect of the fungus on the degradability of dry matter (DM) and organic matter (OM) of corn stover were observed. A randomized complete block with a factorial arrangement of 2x3 (strains * stover) was employed…..